EU (Market) in Sight, Russia at the Gate: Three Decades of Aspiration and Resistance - Kardava, Ekaterine (European Scientific Journal, ESJ, 2025)
Since 1991, Georgia has followed a difficult yet ambitious path. The declaration of independence and the pursuit of a Euro-Atlantic future placed the country before numerous formidable challenges: Russian occupation, economic collapse, hybrid warfare, painful transitions of ruling power, and deep political polarization. Despite these obstacles, Georgia emerged as a leading Eastern Partnership country, implemented notable digital and infrastructure reforms, and secured EU candidacy in 2023. This parallel dual process reflects both the nation’s steadfast commitment to its European choice and the persistent efforts to break its resilience from the North. Georgia’s progress, achieved amid external sabotage, faced renewed destabilization after its inclusion in the EU enlargement package. What war could not accomplish, Russia pursued through media influence, capital inflows, market manipulation, and exploitation of Georgia’s unresolved vulnerabilities, ultimately reorienting its economy. The failure of the DCFTA further weakened Georgia’s European trajectory, while Russian immigration and asset flows reshaped its political landscape. This article questions whether the EU acted too late in opening broader access to the internal market for Georgia. In parallel with political processes, could earlier and more intensive market integration have ensured stability, economic convergence, and social well-being? Instead of a fragmented model, could this have fostered a synchronized process of political, economic, and social Europeanization? Does Georgia’s trajectory reflect not only a national setback, but also a broader failure of the EU’s influence in the region?